Cohort Study of Carbon Black Exposure and Risk of Malignant and Nonmalignant Respiratory Disease Mortality in the US Carbon Black Industry. Issue 9 (September 2015) - Dell, Linda D.; Gallagher, Alexa E.; Crawford, Lori; Jones, Rachael M.; Mundt, Kenneth A.
<x xml:space="preserve">Abstract</x> Objective: To evaluate lung cancer and respiratory disease mortality associations with cumulative inhalable carbon black exposure among 6634 US carbon black workers. Methods: This analysis was performed using standardized mortality ratio (SMRs) and Cox regression analyses. Results: Lung cancer mortality was decreased overall (SMR = 0.77; 95% confidence interval [CI], 0.67 to 0.89) but less so among hourly male workers (SMR = 0.87; 95% CI, 0.71 to 1.05). No exposure–response association was observed with time-dependent cumulative inhalable carbon black: hazard ratio [HR] = 1.0 (95% CI, 0.6 to 1.6) for 20 to less than 50 mg/m3·yr); HR = 1.3 (95% CI, 0.8 to 2.1) for 50 to less than 100 mg/m3·yr; and HR = 1.4 (95% CI, 0.9 to 2.1) for 100 mg/m3·yr or more compared with referent (<20 mg/m3·yr). No consistent associations were observed between cumulative inhalable carbon black exposure and respiratory disease mortality. Conclusion: Quantitative carbon black exposure estimates were not related to lung cancer or nonmalignant respiratory disease mortality.